Pengaruh aroma terapi kopi terhadap intensitas nyeri postpartum Sectio Caesarea (SC) - Fitry Erlin; Busyra Hanim; Fikri Romadhan (Holistik Jurnal Kesehatan, 2023)
Background: Pain caused by cesarean sections (CS) will generally be felt for several days. The pain increased on the first-day post-SC. One way to manage pain can be done in a non-pharmacological way using coffee aromatherapy. Substances contained in coffee such as caffeine and alkaloids can provide energy and physiological effects, such as reducing fatigue or stress.Purpose: To determine the effect of coffee aroma therapy on the pain intensity of postpartum in cesarean sections (CS)Method: A quantitative type of research with a quasi-experimental research design. The number of samples is 15 participants with a total sampling technique. The research instrument was a pain intensity questionnaire. The analysis used was the paired sample T-test (a<0.05).Results: Knowing that there is a difference in the average pain intensity of postpartum in cesarean sections (CS) after having coffee aroma therapy with pain intensity of a mean value from 1.87 to 1.83 and the results of statistical tests obtained a p-value of 0.001.Conclusion: There was effectiveness of coffee aroma therapy in reducing the pain intensity of postpartum in cesarean sections (CS.Keywords: Aromatherapy; Coffee; Pain Intensity; Postpartum; Cesarean Sections (CS).Pendahuluan: Nyeri yang disebabkan oleh Sectio Caesarea (SC) pada umumnya akan terasa hingga beberapa hari. Rasa nyeri tersebut meningkat pada hari pertama post SC. Manajemen untuk mengatasi nyeri dapat dilakukan salah satunya dengan cara non-farmakologis menggunakan aroma terapi kopi. Zat yang terkandung di dalam kopi seperti kafein dan alkaloid dapat memberikan efek fisiologis energi, seperti mengurangi kelelahan atau stress.Tujuan: Untuk mengetahui pengaruh aroma terapi kopi terhadap intensitas nyeri postpartum SC di RSUD Arifin Ahmad Pekanbaru.Metode: Penelitian kuantitatif dengan desain penelitian quasi experiment dan jumlah sampel sebanyak 15 partisipan dengan teknik total sampling. Instrumen penelitian berupa kuesioner intensitas nyeri. Analisa yang digunakan adalah Paired Sampel T-test (a<0.05).Hasil: Diketahui bahwa terdapat perbedaan rata-rata tingkat nyeri postpartum Sectio Caesarea sebelum dan setelah pemberian aroma terapi kopi dengan nilai mean 1,87 turun menjadi 1,83 dan hasil uji statistik diperoleh p-value 0,001.Simpulan: Ada pengaruh aroma terapi kopi terhadap intensitas nyeri postpartum SC di RSUD Arifin Ahmad Pekanbaru.